Program Tahfidz Al-Qur’an Unggulan dalam Membentuk Karakter Religius dan Disiplin Siswa di SMPIT Al-Madinah - Muhammad Farhan Ali; Zaenal Abidin (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the role of the excellent Al-Qur’an memorization program in shaping students’ religious and disciplined character at SMPIT Al-Madinah Boyolali. This research employed a qualitative approach with a field research design. The research subjects consisted of the principal, tahfidz teachers, and students involved in the excellent Al-Qur’an memorization program. Data were collected through observation and interviews. Data validity was tested using technique triangulation and source triangulation. The data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the excellent Al-Qur’an memorization program at SMPIT Al-Madinah Boyolali was implemented systematically through memorization deposit activities, muroja’ah (revision), habituation of Qur’anic reading, recitation guidance using the Al-Jauhari method, and additional activities through the Ashabbul Qur’an Club. This program contributed to shaping students’ religious character through the habituation of reading and memorizing the Qur’an, maintaining proper manners, performing worship, and fostering love for the Qur’an. In addition, the program also played an important role in shaping students’ disciplined character through habituation in following activity schedules, achieving memorization targets, regularly submitting memorization, and obeying program rules. Therefore, the excellent Al-Qur’an memorization program has a significant role in shaping the religious and disciplined character of students at SMPIT Al-Madinah Boyolali.